Which patient may benefit the most from penile prosthesis implantation?. (26th September 2022) - La Croce, Giovanni; Schifano, Nicolò; Pescatori, Edoardo; Caraceni, Enrico; Colombo, Fulvio; Bettocchi, Carlo; Carrino, Maurizio; Vitarelli, Antonio; Pozza, Diego; Fiordelise, Stefano; Varvello, Francesco; Paradiso, Matteo; et al.
Abstract: Background: Penile prosthesis implantation has been associated with overall good functional outcomes. Of relevance, some patients reported higher level of satisfaction and quality of life. Aim: We investigated the profile of the patients who may benefit the most from penile prosthesis implantation. Materials and methods: Data from a national multi‐institutional registry of penile prostheses including patients treated from 2014 to 2017 in Italy (Italian Nationwide Systematic Inventarization of Surgical Treatment for Erectile Dysfunction) were analyzed. All data have been prospectively recorded by 45 surgeons on a dedicated website (www.registro.andrologiaitaliana.it ) and revised by a single data manager. Patients' baseline characteristics were recorded. In order to simultaneously evaluate perceived penile prosthesis function and quality of life, all patients were re‐assessed at 1‐year follow‐up using the validated questionnaire Quality of Life and Sexuality with Penile Prosthesis. High quality of life after surgery was defined as a score higher than the 75th percentile in each of the subdomains of the Quality of Life and Sexuality with Penile Prosthesis questionnaire. Logistic regression analysis tested the association between clinical characteristics and high quality of life after penile prosthesis implantation. Results: Follow‐up data were available for 285 patients (median age 60 years; interquartile range: 56–67) who underwent penile prosthesis implantation. Erectile dysfunction etiology was organic in 40% (114), pelvic surgery/radiotherapy in 39% (111), and Peyronie's disease in 21% (60) of the cases. Patients showed good overall Quality of Life and Sexuality with Penile Prosthesis scores at 1‐year follow‐up for functional (22/25), personal (13/15), relational (17/20), and social (13/15) domains. Overall, 27.0% (77) of patients achieved scores consistent with the high quality of life definition. These patients did not differ in terms of median age (60 vs. 62), type of prosthesis (inflatable penile prostheses: 95% in both of the cases), and post‐operative complications (10% vs. 14%) than those with lower quality of life score (all p  > 0.1). At logistic regression analysis, erectile dysfunction etiology was the only factor independently associated with high quality of life at 1 year after surgery ( p  = 0.02). Patients treated for Peyronie's disease (odds ratio: 2.62; p  = 0.01; 95% confidence interval: 1.20–5.74) were more likely to report better outcomes after accounting for age, post‐operative complications, and surgical volume. Conclusion: Penile prosthesis implantation is associated with an overall good quality of life. The subset of patients affected by erectile dysfunction secondary to Peyronie's disease seemed to benefit the most from penile prosthesis implantation in terms of functional outcomes, relationship with their partners and the outside world, and perceived self‐image. The systematic use of validated questionnaires specifically addressed at evaluating quality of life and satisfaction after penile prosthesis implantation should be further implemented in future studies to better define the predictors of optimal satisfaction after penile prosthesis implantation.